#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# If tan teta+sinteta=m,tanteta=m,tanteta-sinteta=n and m is not equal n then prove that m2-n2=4rootmn

3 years ago

Given :- (1)  TanA + SinA = m

(2)  TanA - SinA = n

To prove :- m2 - n2 = 4  x  (root mn)

Proof :-

L.H.S =  m2 - n2

= (TanA + SinA)2 - (TanA - SinA)2

= (Tan2A + Sin2A + 2 TanA SinA) - ( Tan2A + Sin2A - 2 TanA SinA)

= Tan2A + Sin2A + 2 TanA SinA - Tan2A - Sin2A + 2 TanA SinA

= Tan2+ Sin2+ 2 TanA SinA - Tan2A  - Sin2A + 2 TanA SinA

= 4 TanA SinA

R..H.S ;- 4 root mn

= 4 x [ root (TanA + SinA)(TanA - SinA) ]

= 4 x [ root ( Tan2A - Sin2A ) ]

= 4 x [ root ( Sin2A / Cos2A  -  Sin2A )

= 4 x [ root { (Sin2A - Sin2ACos2A) / Cos2A } ]

= 4 x [ root { Sin2A (1 - Cos2A) } / Cos2A ]

= 4 x [ root { (Sin2A  x  Sin2A ) / Cos2A ]

= 4 x (root [ Sin2A Tan2A ] )

= 4 TanA SinA = L.H.S

Hence Proved